Genome-Wide Characterization of Arabian Peninsula Populations: Shedding Light on the History of a Fundamental Bridge between Continents. (21st January 2019) - Fernandes, Veronica; Brucato, Nicolas; Ferreira, Joana C; Pedro, Nicole; Cavadas, Bruno; Ricaut, François-Xavier; Alshamali, Farida; Pereira, Luisa
Abstract: The Arabian Peninsula (AP) was an important crossroad between Africa, Asia, and Europe, being the cradle of the structure defining these main human population groups, and a continuing path for their admixture. The screening of 741, 000 variants in 420 Arabians and 80 Iranians allowed us to quantify the dominant sub-Saharan African admixture in the west of the peninsula, whereas South Asian and Levantine/European influence was stronger in the east, leading to a rift between western and eastern sides of the Peninsula. Dating of the admixture events indicated that Indian Ocean slave trade and Islamization periods were important moments in the genetic makeup of the region. The western–eastern axis was also observable in terms of positive selection of diversity conferring lactose tolerance, with the West AP developing local adaptation and the East AP acquiring the derived allele selected in European populations and existing in South Asia. African selected malaria resistance through the DARC gene was enriched in all Arabian genomes, especially in the western part. Clear European influences associated with skin and eye color were equally frequent across the Peninsula.